Pengaruh Motivasi, Lingkungan dan Pengalaman Kerja Terhadap Loyalitas Karyawan Pamella 9 Supermarket Wonosari - Yuanika Asmarani Utami; Uswatun Chasanah (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The retail industry is one of the choices for people to fulfill their needs. With the dynamics of the retail industry that had slumped, one of the local retailers in Yogyakarta, Pamella Supermarket, became the favorite choice of the people of Yogyakarta. One of the Pamella Supermarket branches, Pamella 9 Supermarket Wonosari, is always crowded with customers and its existence absorbs the youth workforce of Gunungkidul area. The existence of competition in this industry requires many supporting factors to survive. In this study, several important factors are examined, including work motivation, work environment, work experience and employee loyalty. This study aims to analyze the simultaneous influence of work motivation, work environment and work experience on employee loyalty at the Pamella 9 supermarket in Wonosari. The research data was collected from 60 respondents through interviews and questionnaires. To analyze the data obtained, multiple linear regression techniques were used and processed with SPSS version 27.The results showed some important conclusions: first, work motivation did not have a significant influence; second, the work environment had a positive and significant influence; third, work experience also had a positive and significant influence; fourth, overall, work motivation, work environment and work experience had a significant effect on employee loyalty at Pamella 9 Supermarket in Wonosari.